Colossal positive magnetoresistance in surface-passivated oxygen-deficient strontium titanite - David, Adrian (2015)
Modulation of resistance by an external magnetic field, i.e. magnetoresistance effect, has been a long-lived theme of research due to both fundamental science and device applications. Here we report colossal positive magnetoresistance (CPMR) (>30,000% at a temperature of 2 K and a magnetic field of 9 T) discovered in degenerate semiconducting strontium titanite (SrTiO3) single crystals capped with ultrathin SrTiO3/LaAlO3 bilayers. The low-pressure high-temperature homoepitaxial growth of several unit cells of SrTiO3 introduces oxygen vacancies and high-mobility carriers in the bulk SrTiO3, and the three-unit-cell LaAlO3 capping layer passivates the surface and improves carrier mobility by suppressing surface-defect-related scattering. The coexistence of multiple types of carriers and inhomogeneous transport lead to the emergence of CPMR. This unit-cell-level surface engineering approach is promising to be generalized to others oxides, and to realize devices with high-mobility carriers and interesting magnetoelectronic properties.